2011
DOI: 10.1093/ecam/nep111
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Bangladeshi Medicinal Plant Extracts

Abstract: To investigate the cytotoxic effect of some Bangladeshi medicinal plant extracts, 16 Bangladeshi medicinal plants were successively extracted with n-hexane, dichloromethane, methanol and water. The methanolic and aqueous extracts were screened for cytotoxic activity against healthy mouse fibroblasts (NIH3T3) and three human cancer-cell lines (gastric: AGS; colon: HT-29; and breast: MDA-MB-435S) using the MTT assay. Two methanolic extracts (Hygrophila auriculata and Hibiscus tiliaceous) and one aqueous extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 45 publications
3
84
0
1
Order By: Relevance
“…(Uddin et al, 2009). Several recent studies have investigated the cytotoxicity of natural plant extracts against human cervical and breast cancer cell lines (MCF-7 and HeLa) (Hamedeyazdan et al, 2012;Zhao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…(Uddin et al, 2009). Several recent studies have investigated the cytotoxicity of natural plant extracts against human cervical and breast cancer cell lines (MCF-7 and HeLa) (Hamedeyazdan et al, 2012;Zhao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the fact that anticancer activity of plants has been verified to be connected with a variety of phytochemicals, such as polyphenols, flavonoids and catechins (Uddin et al, 2009), many researchers had also confirmed higher phenolic content of plant materials increases the antioxidant activity of the plant since there is a linear correlation between phenolic contents and antioxidant activity (Rietjens et al, 2005;Ravikumar et al, 2008;Rahman et al, 2011). Although plant phenolics are good source of antioxidants, they differ in their abilities to quench various free radicals, so as verifying the exact role of these phytochemicals in certain kind of an oxidative stress related diseases is of substantial importance.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of CPHP and CAP were tested against monkey kidney cells using the MTT assay according to the method described previously [20]. The IC 50 values were calculated with probit analysis software [21].…”
Section: Mtt Cytotoxicity Assaymentioning
confidence: 99%